The CRESST-III low-mass WIMP detector. Issue 4 (May 2016) - Strauss, R; Angloher, G; Bento, A; Bucci, C; Canonica, L; Defay, X; Erb, A; von Feilitzsch, F; Ferreiro Iachellini, N; Gorla, P; Gütlein, A; Hauff, D; et al.
Abstract: The next generation direct dark matter experiment CRESST-III has a high potential to significantly increase the sensitivity to low-mass WIMPs ( mx ≲10GeV/c 2 ). We present the new CRESST detector module: it consists of a 24 g CaWO4 crystal operated as a phonon detector and a 20×20 mm 2 silicon-on-sapphire light detector. The phonon energy threshold is lowered to 100eV and a light detector resolution of typically 5eV is achieved. A fully-scintillating inner detector housing is realised which efficiently rejects events from surface-alpha decays. The CaWO4 sticks holding the target crystal are also operated as calorimeters to discriminate all possible artefacts related to the support structure. A projection for the sensitivity to spin-independent WIMP-nucleon scattering is given for the first phase of CRESST-III which will start beginning of 2016.